2021
DOI: 10.3390/nano11123406
|View full text |Cite
|
Sign up to set email alerts
|

Release of Nanoparticles in the Environment and Catalytic Converters Ageing

Abstract: A Three-Way Catalyst (TWC) contains a cordierite ceramic monolith coated with a layer of Al2O3, CexZr1−xO2 and platinoids mixture. Under standard operation, the platinoid concentration decreases, exposing the remaining washcoat structure. After that particle release stage, the sintering process follows where the crystalline CexZr1−xO2 solution is broken and begins to separate into ZrO2 and CeO2 phases. ZrO2 is released to the environment as micro and nanoparticles, while a small amount of CeO2 generates a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(77 reference statements)
0
4
0
2
Order By: Relevance
“…The presence of Zr at concentrations above LGB in the riverbank is relevant since there are no Zr-sources other than traffic in the area. Previous studies have shown the strong correlation of Ce and Zr in road dust collected at high traffic areas (Meza-Figueroa et al, 2021) and the Raman signature of ceria-zirconia particles (Navarro-Espinoza et al, 2021). Even though we did not obtain the total Ce composition of sediments, the UFP composed of Ce-Zr was identified by Raman spectroscopy and supported by the SEM-EDS analysis.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The presence of Zr at concentrations above LGB in the riverbank is relevant since there are no Zr-sources other than traffic in the area. Previous studies have shown the strong correlation of Ce and Zr in road dust collected at high traffic areas (Meza-Figueroa et al, 2021) and the Raman signature of ceria-zirconia particles (Navarro-Espinoza et al, 2021). Even though we did not obtain the total Ce composition of sediments, the UFP composed of Ce-Zr was identified by Raman spectroscopy and supported by the SEM-EDS analysis.…”
Section: Discussionmentioning
confidence: 68%
“…The elements Zr-Cu-V-Sb-Nb-Y-Fe have been previously described by Navarro-Espinoza et al (2021) as contaminant elements in TWCC that promote the detachment of the refractory washcoat made of Zr-Ce. This process is crucial for the release of UFP to the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adicionalmente, algunos elementos químicos presentes en los aditivos de las gasolinas se pueden incorporar a la superficie catalítica [18]. En algunos casos, las unidades convertidoras se sobrecalientan derritiendo la estructura interna de panal [19]. Por otra parte, el empuje a alta presión del flujo de gases y el golpeteo generado por el mal estado de calles y carreteras puede producir su desintegración, liberando la capa catalizadora a la atmósfera [16].…”
Section: Importancia De Su Uso Y Reemplazounclassified